Wie wirken gemeldete SPS-Maßnahmen? Ein Gravitationsmodell des EU-Rindfleischhandels - Marc Kramb; Roland Herrmann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2009)
(...) In diesem Beitrag werden Meldungen über SPS-Maßnahmen bei der WTO herangezogen, um Handelswirkungen von sanitären und phytosanitären Handelsbeschränkungen zu messen. Die WTO-Datenbank der SPS-Meldungen wird erläutert. Es wird dann ein Gravitationsmodell verwendet, um für das Beispiel des EU-Rindfleischhandels zu untersuchen, wie im Zeitraum Januar 1995 bis Juni 2001 die im Zusammenhang mit BSE eingeführten SPS-Maßnahmen von Nicht-EU-Mitgliedern gegenüber der EU den bilateralen Handel beeinflusst haben. 31 potenziell betroffene Produktgruppen werden unterschieden, und mit einem Fixed-Effects-Ansatz werden die Paneldaten ausgewertet. Es zeigt sich, dass SPS-Maßnahmen im Zusammenhang mit BSE die Rindfleischexporte der EU in den wichtigsten Produktkategorien reduziert haben. Sie wirkten allerdings nicht wie ein Handelsverbot - der prozentuale Erlösrückgang lag unter 100 % und betrug z. B. 49 % bei lebenden Rindern, 74 % bei frischem und gekühltem Fleisch und 86 % bei gefrorenem Fleisch. Da in einer ganzen Reihe von Produktgruppen die Exporte von Rindern, Rindfleisch und verwandten Produkten um deutlich weniger als 100 % sanken, ist offenbar der beantragte SPS-Handelseingriff deutlich stärker als die vom Importland umgesetzte Handelsbeschränkung. In künftigen Studien zum SPS-Abkommen muss daher zwischen SPS-Meldungen und SPS-Maßnahmen unterschieden werden. (Quelle: Verlag). – – For decades, nontariff trade barriers (NTBs) have been regarded as more problematic policy instruments than tariffs in international trade negotiations. This is due to the fact that trade impacts of nontariff trade barriers are less transparent than those of tariffs. Tariffication of nontariff agricultural trade barriers was finally decided under the Uruguay Round of GATT. Although the OECD concluded that a reduction of NTBs took place after 1994, this finding can be challenged. First, tariff-rate quotas (TRQs) are not counted as NTBs by law although they cause effects similar to those of quotas. The number of TRQs has increased strongly after the Uruguay Round. Second, sanitary and phytosanitary measures, i.e. SPS measures, have become more important as notifications under the SPS Agreement do show. There are only few empirical studies available which analyze the effects of these SPS measures.WTO Notifications under the SPS Agreement are utilized in this contribution for measuring trade impacts of sanitary and phytosanitary trade barriers. We explain the WTO data base on SPS notifications. Then, a gravitation model is applied to the EU beef trade in the period January 1995 to June 2001. It is investigated how SPS measures, introduced by non-EU countries in the context of BSE, affected bilateral trade with the EU. We distinguish between 31 product groups which might be affected, and a fixed-effects model is used for analyzing the panel data. We elaborate that SPS measures related to BSE reduced EU beef export revenues in the major product categories significantly. The NTBs did not reduce exports to zero, however, as might have been expected. The percentage reduction of export revenues was 49 % for live cattle, 74 % for fresh and cooled beef and 86 % for frozen beef. For most other product groups, the percentage decline in sales was significant but lower in percentage terms. Apparently, SPS notifications indicate that bilateral trade is restricted but it does not definitely show that the notified measures by the importing country are actually implemented and for which time period. It seems very important in future analyses of the SPS measures to distinguish carefully between SPS notifications and SPS measures.
Keywords: 330; Rindfleisch; Exportbeschränkung; Tierkrankheit; WTO-Recht; Nichttarifäre Handelshemmnisse; Gravitationsmodell; EU-Staaten; Welt